White dwarf luminosity and mass functions from sloan digital sky survey spectra - DeGennaro, Steven (2008)
We present the first phase in our ongoing work to use Sloan Digital Sky Survey (SDSS) data to create separate white dwarf (WD) luminosity functions (LFs) for two or more different mass ranges. In this paper, we determine the completeness of the SDSS spectroscopic WD sample by comparing a proper-motion selected sample of WDs from SDSS imaging data with a large catalog of spectroscopically determined WDs. We derive a selection probability as a function of a single color (g - i) and apparent magnitude (g) that covers the range -1.0 < g - i < 0.2 and 15 < g < 19.5. We address the observed upturn in log g for WDs with Teff≲ 12,000 K and offer arguments that the problem is limited to the line profiles and is not present in the continuum. We offer an empirical method of removing the upturn, recovering a reasonable mass function for WDs with Teff< 12,000 K. Finally, we present a WD LF with nearly an order of magnitude (3358) more spectroscopically confirmed WDs than any previous work.